PRINSIP PERLINDUNGAN AKTIF TERHADAP DATA PRIBADI - Bakhtiar, Nur Muh. Aldi; Laman, Ilham (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2024)
This research aims to find out the principle of active protection of personal data. The problem in this research is the rampant cases of personal data breaches in Indonesia. The research method used is library reasearch. The data sources used are primary data sources in the form of laws and regulations, al-Qur’an, hadith and theories and secondary data in the form of books, journals, theses or papers relevant to this research. The results of this study explain that, The role in the law is to define personal data criteria then control personal data, determine the control of personal data both public bodies and international organizations and determine the subject of personal data related to the right to destruction and electronic systems. The principle of active protection of personal data is that the first personal data is privacy and determines the special authority institution that protects personal data and provides special protection both administratively and criminally.